Note on the Size Groups of Prawns Landed by Shrimp Trawls of Four Different Cod end Meshes - Satyanarayana, A V V (Fishery Technology, 1965)
Note on the Size Groups of Prawns Landed by Shrimp Trawls of Four Different Cod end Meshes